Somatic, positive and negative domains of the Center for Epidemiological Studies Depression (CES-D) scale: a meta-analysis of genome-wide association studies. Issue 8 (21st March 2016) - Demirkan, A.; Lahti, J.; Direk, N.; Viktorin, A.; Lunetta, K. L.; Terracciano, A.; Nalls, M. A.; Tanaka, T.; Hek, K.; Fornage, M.; Wellmann, J.; Cornelis, M. C.; et al.
Abstract : Background: Major depressive disorder (MDD) is moderately heritable, however genome-wide association studies (GWAS) for MDD, as well as for related continuous outcomes, have not shown consistent results. Attempts to elucidate the genetic basis of MDD may be hindered by heterogeneity in diagnosis. The Center for Epidemiological Studies Depression (CES-D) scale provides a widely used tool for measuring depressive symptoms clustered in four different domains which can be combined together into a total score but also can be analysed as separate symptom domains. Method: We performed a meta-analysis of GWAS of the CES-D symptom clusters. We recruited 12 cohorts with the 20- or 10-item CES-D scale (32 528 persons). Results: One single nucleotide polymorphism (SNP), rs713224, located near the brain-expressed melatonin receptor ( MTNR1A ) gene, was associated with the somatic complaints domain of depression symptoms, with borderline genome-wide significance ( p discovery = 3.82 × 10 −8 ). The SNP was analysed in an additional five cohorts comprising the replication sample (6813 persons). However, the association was not consistent among the replication sample ( p discovery+replication = 1.10 × 10 −6 ) with evidence of heterogeneity. Conclusions: Despite the effort to harmonize the phenotypes across cohorts and participants, our study is still underpowered to detect consistent association for depression, even by means of symptom classification. On the contrary, the SNP-based heritability and co-heritability estimation results suggest that a very minor part of the variation could be captured by GWAS, explaining the reason of sparse findings.